Proses penyahnitratan dan penyahwamaan di dalam reaktor lapisan terkembang - Siti Kartom Kamarudin,; Rakmi Abdul Rahman, (2001)
Synthetic textile wastewater was biologically treated in aerobic and anaerobic expanded bed reactors. The objectives of this study are to investigated the reduction of COD (Chemical Oxygen demand), denitrification process, decolourisation process and other related parameters. Experimental work was done using perspec columns resctors which were innoculated with mixed culture. Granulated activated carbon was used as a support medium. Samples were analysed for their outlet and inlet COD, outlet and inlet nitrate, pH, temperature and biomass. It was observed that, a good removal of COD, nitrate and colour were obtained. The results shows that aerobic condition with dissolved oxygen less than 2.0 mg/L could reduce the accumulation of toxid on the biofilm surface and could 'increase the efficiency of COD reduction as well as denitrification and decolourisation process for a longer period. The results also proved that simulatenous biodecolourisation and biodenitrification could a single reactor for both systems